Pengaruh Reference Group dan Online Costumer Review Terhadap Minat Beli di Kei Hobby Shop (Studi Kasus Komunitas Facebook Kei Hobby Shop) - Bryan Javin Santoso; Joseph M.J. Renwarin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of the Reference Group and Online Customer Review on buying interest in the Kei Hobby Shop. There are three variables in this study that include the Reference Group, Online Customer Review and buying interest. Researchers used quantitative methods and samples used in this study amounted to 151 respondents who knew the Kei Hobby Shop. The technique used in this study was purposive sampling which was part of non probability sampling. The research data analyzed using SPSS 21 showed that the Reference Group variable had influence on buying interest and the variable Online Customer Review has an influence on buying interest in Kei Hobby Shop.